Faktor-Faktor Yang Mempengaruhi Minat Nasabah Menggunakan Mobile Banking Bank BJB Syariah - Wibowo, Hari; Rahmawati, Rafika; Mardiah, Siti (LPPM Universitas Islam 45, 2024)
The development of technology-based systems, especially those related to the internet, affects financial institutions (banks) in interacting with customers. Mobile banking has become one of the self-service that allows banks to provide information services and convenience to customers, through mobile banking customers can get several benefits, namely banking services that are fast, safe, cheap, available at any time and can be accessed from anywhere. Therefore, the purpose of this study is to determine the factors that influence customer interest in using mobile banking at Bank BJB Syariah Bekasi Branch. This study uses a quantitative method with data collection using a questionnaire questionnaire with a population of all customers who use mobile banking at Bank BJB syariah Bekasi Branch. banking at Bank BJB Syariah Bekasi Branch with the sampling technique using purposive sampling. sampling technique using purposive sampling. The data analysis method used is multiple linear regression analysis using the help of IBM SPSS software version 16. The results showed that partially perceived benefits and perceived ease of use had no significant effect on customer interest in using mobile banking at Bank BJB Syariah Bekasi Branch, while perceived credibility and information about mobile banking had a significant positive effect on customer interest in using mobile banking. have a significant positive effect on customer interest in using mobile banking at Bank BJB Syariah Bekasi Branch.